COMMUNITY PERCEPTIONS OF THE EXPANSION AREA VILLAGE KEMANTAN KEBALAI DISTRICT OF AIR HANGAT TIMUR REGENCY KERINCI - Anggraini, Meti; Erita, Yeni; U, Iswandi (STKIP PGRI Sumbar, 2013)
Expansion of intensive rural area to date has been developed in Indonesia as one way for equitable development and improve peoples welfare. Development of a region is generally caused by both natural population growth and migration as well as an increase in the activities of the residents in the area as a container utilizing its development. Splitting of the village is essentially an attempt to improve the welfare of the people still refer to the economic growth by taking into account the carrying capacity of the region, both in terms of the community service aspects, aspects of governance, development aspects and aspects of the regions potential. Rural area development will have a positive impact for the betterment of society. This study aims to determine the Regional Public Perceptions About Redistricting at the village Kemantan Kebalai district of Air Hangat Timur Regency Kerinci.This research is descriptive. Descriptive research will reveal problems that occur in the present as they are. Population in this research is the head of the family living in the the village Kemantan Kebalai district of Air Hangat Timur Regency Kerinci. Samples were taken by way of proportional sampling. Respondent sample taken with random sampling techniques with the proportion of 25%, totaling 86 samples. Analysis using the analysis of the percentage formula. Techniques of data collection through questionnaire or instrument.The research found that: 1) Community perceptions of the potential the village Kemantan Kebalai district of Air Hangat Timur Regency Kerinci is quite good with the level of achievement of 70.02%. 2) Community perceptions of the development the village Kemantan Kebalai district of Air Hangat Timur Regency Kerinci is quite good with the level of achievement of 73.05%. 3) Community perceptions of village governance Kemantan Kebalai district of Air Hangat Timur Regency Kerinci classified as less well with the level of achievement of 66.54%. 4) Community perceptions of the public service village Kemantan Kebalai district of Air Hangat Timur Regency Kerinci classified as less well with the level of achievement of 63.95%.